MODELING AND ANALYSIS OF PITCH ANGLE CONTROL ON VARIABLE SPEED WIND TURBINES - Perçin, Hasan Bektaş; Çalışkan, Abuzer (Hibetullah KILIÇ, 2021)
Nowadays, due to the increasing demand for electrical energy, innovative searches continue. Investments in renewable energy, which is used to meet this demand, increasingly continue. Wind energy, which is one of these renewable energy types, has many advantages such as low environmental impact, renewable structure and decreasing system costs with developing technology. However, the instantaneous changes due to the nature of the wind affect the sustainability of the energy obtained from this source and the production efficiency negatively. Maximum efficiency, stable and long-lasting operation is aimed in systems with permanent magnet synchronous generators (PMSG), whose use in wind energy is increasingly widespread, according to the instant wind. In line with these objectives, systems should be used with appropriate control structures. Modelling studies that can be done in the computer environment, give the opportunity to see the effect of the controls to be used in energy conversion structures, which can be difficult and costly to work on the real system. This provides the result of the adjustments that can be conducted in the system before installation, to analyze and compare various parameters. Thus, with the adjustments, the problems that may occur after the installation can be prevented, higher performance and less costly designs can be achieved. In this study, the basic components and parameters of the wind energy system are explained and mathematical models of these parameters are obtained. The working principle of the control structures that can be used in the system is explained through these expressions. The general system modelling, which includes pitch angle control designed to be activated at higher wind speeds, was designed in Matlab/Simulink environment, and graphical analysis of the control structure was performed based on various system parameters. As a result, the control structure ensures stable operation of the system at higher wind speeds.
Keywords: Electrical Engineering; Elektrik Mühendisliği